NICHE MARKET: RESPONSE OF STUDENTS OF BUDDHIST DHARMA UNIVERSITY ON KAWASAKI BRAND MOTORCYCLES : CERUK PASAR : TANGGAPAN MAHASISWA UNIVERSITAS BUDDHI DHARMA PADA MOTOR MEREK KAWASAKI - Sonny Santosa (Yayasan Education and Social Center, 2021)
Currently, the growth of motor vehicle market share is increasing in the global market including In Indonesia, one of the motorcycle brands that attract market share in the community is Kawasaki motorcycles, especially Kawasaki motorcycle type W175, this type of motorcycle is classified as a retro motorcycle that has quite a lot of enthusiasts of this type of motorcycle, this study was conducted to see the market share opportunities for a